Meningkatkan Keadilan Sosial Ekonomi melalui Implementasi Akhlaq dalam Hukum Islam: Implementasi Akhlaq dalam Hukum Islam - Kusyana, Kusyana; Romlah, Romlah (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This research aims to explore the potential of enhancing socioeconomic justice through the implementation of morality within Islamic law. Using a qualitative approach, this study analyzes the relevant concepts of morality and principles of Islamic law in the economic context. The findings indicate that principles such as justice, honesty, and social responsibility play a crucial role in creating a more equitable and inclusive economic system. The research also identifies several challenges in implementing morality within the framework of Islamic law, including the lack of understanding and awareness among the public about these concepts, as well as the complexity of adapting them to the modern economic context. Therefore, collaborative efforts from various stakeholders, including government, civil society, and the private sector, are needed to address these challenges and promote the implementation of moral principles within Islamic law in everyday economic life. Keywords: socioeconomic justice, morality, Islamic law, inclusive, collaborative